Efeito de diferentes tratamentos utilizados em sistemas agroecológicos no controle de danos da Diabrotica speciosa (Germar) (Coleoptera: Chrisomelidae) em feijão-vagem (Phaseolus vulgaris L.) - Astolphi Filho, Guithembergue (2016)
The snap bean crop, Phaseolus vulgaris L., is one of the most important undertaken by farmers, and its fruit much appreciated by oleraceous consumers. Most of the pest control is carried out with the application of pesticides, endangering consumer health. The main pests that occur in snap bean crop, leaf beetle, Diabrotica speciosa (Germar) (Coleoptera: Chrisomelidae), is one of the most important, causing reduction in leaf area and photosynthetic capacity of the plant, compromising productivity. This study aimed to evaluate the percentage of defoliation, fruit punch and productivity in snap bean crop, cultivar trepador noodle indeterminate growth under attack D. speciosa, subjected to different treatments used in organic agriculture. Lime sulfur were tested (12.5 g / L), the homeopathic nosode insect pests 4CH (1 mL / L), the biodynamic prepared P501 (0.06 g / L) and the entomopathogenic fungus Beauveria bassiana (Bals .) Vuillemin (15 g / L). Were carried out in 10 central plants of each plot, reviews percent defoliation at 50 days after emergence, and fruit punch from 10 days after fruiting, considering the median third of the plants through diagrammatic scale. commercial fruit production analysis also was performed, considering its dry matter in the corresponding period. It was found in the experiment that all productes had control in defoliation analysis and drilled fruits regarding witness treatments. In defoliation analysis pointed to lime sulfur and the fungus B. bassiana. None of the inputs influenced the final production which was obtained commercial income below average.